A review of research on teacher competencies in higher education. Issue 2 (18th January 2022) - Dervenis, Charalampos; Fitsilis, Panos; Iatrellis, Omiros
Abstract : Purpose: The purpose of this paper is to thoroughly assemble, analyze and synthesize previous research to investigate and identify teaching staff competencies derived from the roles and tasks attributed to university professors. Design/methodology/approach: In this literature review, the authors looked at both the conceptual framework exploring the educational concepts and the learning theories focusing on teaching staff roles and competencies in higher education. Thirty-nine scientific papers were studied in detail from a total of 102 results, which were eligible based on the preferred reporting items for systematic reviews and meta-analyses statement. Findings: A multi-dimensional approach to teacher competencies in higher education was proposed, which consists of six main dimensions with their respective characteristics. Thirty-two discrete teaching staff competencies were identified and distributed in the aforementioned dimensions. The research revealed that specific competencies, such as the digital competence of teachers, which have lately become of high importance worldwide due to the COVID-19 pandemic implications, surprisingly, until recently, they were considered secondary in the educational process. Research limitations/implications: The study was based on the existing literature without using data drawn from an appropriate questionnaire addressed to students and/or interviews with academics. In addition, in an effort to maintain a homogeneous base of teacher competencies, inclusion of domains of expertise was avoided. Further research should focus on designing and developing a holistic model using analytical learning approaches that will contribute to the assessment of teachers' competencies and explore the relationship of these competencies to students' academic achievement, contributing quality to higher education. Practical implications: A specific framework of teacher competencies in higher education, in practice, can be a useful reference point not only for ensuring quality in the selection of teachers and their career-long professional development but also for national education policy strategies. The definition of teacher competencies framework contributes to facilitating effective dialogue for the evaluation and quality assurance in education between agencies, authorities, researchers, teachers, policymakers, education managers and different communities at large. Social implications: These competencies are at the heart not only of the teaching and learning process but also in the workplace and in society in general and are increasingly recognized as essential. An adequately prepared community and management equipped with the required employee competencies is able to react immediately and in a positive way to any obstacle, yielding optimal results. Originality/value: This is the first review, to the authors' knowledge, to comprehensively explore the literature to identify, classify and rank the teaching staff competencies in higher education, revealing the gap between perceived and actual importance of various competencies.